EEG Activity During Mental Influence on a Random Signal Generator - Giroldini, William (Journal of Scientific Exploration, 2021)
This preliminary study is based on 38 experimental sittings in which 22 participants attempted to mentally influence an electronic circuit called RSG (Random Signal Generator), while their cerebral activity was recorded by a 14-channel EEG. Subject to sampling, signal peaks with an absolute value greater than a predetermined threshold were selected from the analogical RSG output by a computer program. Whenever a signal exceeded the threshold, an audible ‘beep’ sounded and the participant was asked to mentally increase the frequency of these beeps as much as possible, because a higher beep rate meant a successful mental influence attempt on the RSG. An important objective was to verify the existence of any relationship between a successful mental influence of the RSG and cerebral activity in the participant attempting the influence. Compared to an equal number of ‘inactive’ sittings made without anyone attempting mental action, the ‘active’ sittings show a small increase in the average number of beeps/minute, but in particular a significant increase in the emitted beeps within 1.5 seconds of the previous beep (P <0.025). The experimental sittings were divided into two groups (around 50% each), of which the first had better results, and only the frontal and fronto-temporal symmetrical EEG locations (AF3, AF4, F7, F8, F3, F4, Fc5, Fc6) were examined. The better group showed a significant reduction in Brain Synchrony (P < 0.03) together with an equally significant increase in Beta and Gamma 15-42 Hz (P < 0.03) activity. These differences were interpreted as an effect of greater mental work performed by the better group during mental influence of the RSG. This is the first study to investigate the relationship between EEG activity and mind-matter (PK) interaction at a distance; indeed all studies devoted to PK have only focused attention on the object of attempted mental action, which was predominantly an RNG (Random Number Generator).